Changes in Safety Net Use During the Great Recession - Anderson, Patricia M.; Butcher, Kristin F.; Schanzenbach, Diane Whitmore (American Economic Review, 2015)
We examine how participation in social safety net programs differs by income-to-poverty levels, and how that relationship changed after the Great Recession. We define income-to-poverty based on the average of 2 years of merged CPS data, and investigate program participation among households with income less than 300 percent of poverty. We find changes in both the level and distribution of safety-net program participation during the Great Recession, with SNAP expanding most at the bottom, the EITC expanding most in the middle, and UI expanding most at the top of the income ranges that we investigate; TANF did not expand.